2012
DOI: 10.21059/buletinpeternak.v34i1.107
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Fisik dan Sensoris Daging Ayam Broiler yang Diberi Pakan dengan Penambahan Ampas Virgin Coconut Oil (VCO) (Physical and Sensory Quality of Meat of Broiler Chicken Fed with The Addition of Virgin Coconut Oil Waste)

Abstract: INTISARIPenelitian ini bertujuan untuk mengetahui kualitas fisik dan sensoris daging ayam broiler yang diberi pakan dengan penambahan ampas virgin coconut oil (VCO). Sebanyak 125 ekor DOC ayam broiler unsex strain Arbor Acres CP 707, dibagi secara acak menjadi 25 kandang masing-masing lima ekor. Ayam dipelihara selama 35 hari. Level ampas VCO dalam perlakuan pakan yaitu: 0, 0,5, 1,0, 1,5, dan 2,0%. Masing-masing perlakuan dengan 5 replikasi kandang. Air minum dan pakan diberikan secara ad libitum. Pada minggu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
2
15
0
7
Order By: Relevance
“…However, generally panellists use their fingers to determine the texture of broiler chicken. With increasing age, the level of roughness of texture will increase [21]. Muscles with small muscle fibres did not show a marked increase in texture roughness with increasing age.…”
Section: P1mentioning
confidence: 82%
“…However, generally panellists use their fingers to determine the texture of broiler chicken. With increasing age, the level of roughness of texture will increase [21]. Muscles with small muscle fibres did not show a marked increase in texture roughness with increasing age.…”
Section: P1mentioning
confidence: 82%
“…According to Jiang et al, [ 71 ] pH 24 varied between 6.01 and 6.06, which is consistent with the average final pH of broiler breast meat (6.03) [ 72 ]. A total of 2% coconut oil in the feed resulted in breast pH [ 73 ], which is not similar to the results of Zhang et al [ 74 ] and Gao et al [ 75 ] with sodium butyrate. Ogunwole et al [ 76 ] measured the effect of 2% coconut oil and 2% palm oil in feed separately.…”
Section: Meat Quality Parametersmentioning
confidence: 91%
“…Abdullah et al [ 77 ] found that the L* value for broilers slaughtered on day 42 was 53.35. Prayitno et al [ 73 ] did not experience differences in color in groups with different percentages (0–2%) of coconut oil. The other color parameters were not affected by the supplementation.…”
Section: Meat Quality Parametersmentioning
confidence: 99%
“…Perlakuan P2 memiliki skor ketertarikan tertinggi yaitu 2,94 kemudian perlakuan kontrol, P1, dan P3 memiliki skor masing-masing 2,73; 2,78; dan 2,68. Ketertarikan responden terhadap daging tergantung pada respons fisiologis dan sensoris setiap individu (Prayitno et al, 2010)…”
Section: Uji Organoleptikunclassified